Synthesis, Characterization and Evaluation of Thiourea Derivatives for Cytotoxicity of Breast Cancer - KT, Awad; AL-Salman, H. N. K.; Najm, Mazin A.A. (Indonesian Journal on Health Science and Medicine, 2025)
Background: Breast cancer is the leading cause of death in women worldwide and the second most common cause in the US. Rescovitine a clinical CDK2 inhibitor has been studied as a potential anticancer agent in breast cancer. has a short half-life (2–5 h), necessitating new analogs with improved pharmacokinetics. Objective: To design and synthesize five thiourea derivatives (VIa–VIe) that mimic rescovitine selectivity and low toxicity, while addressing its pharmacokinetic limitations. Evaluation the cytotoxicity in MCF-7 breast cancer cells. Materials & Methods: Derivatives were synthesized by reacting substituted benzoic acids with SOCl2, followed by the formation of isothiocyanates (IIa–e). Subsequent reflux with 5-amino-1H-pyrazole-4-carbonitrile yielded the thioureas VIa–VIe. Characterization: Melting points, NMR (¹H/¹³C), FT-IR spectroscopy, and EI-MS. antiproliferative activity against MCF-7 cell (MTT assay, IC₅₀), compared to rescovitine. Results: VIa and VIe showed best MCF-7 inhibition (93.77%, IC₅₀ = 123.64 μM; 94.55%, IC₅₀ = 118.49μM) vs. rescovitine (97.33%, IC₅₀ = 20.27μM). VIe (4-F substituent) and VIa (unsubstituted) exhibited strongest cytotoxicity against. All compounds complied with Lipinski’s Rule of Five (0 violations) and showed excellent GI absorption but no BBB permeability. Electronic substituents (e.g., F in VIe) enhanced the activity, while steric groups (e.g., CH₃ in VIb) reduced the efficacy. Conclusion: VIa and VIe emerged as lead candidates with cytotoxicity comparable to that of rescovitine. Fluorine substitution (VIe) optimized the activity, highlighting structure-activity relationships for future to get more potent molecules. Highlights: Lead Compounds Identified: VIa and VIe demonstrated strong antiproliferative activity in MCF-7 cells, approaching that of rescovitine, despite higher IC₅₀ values. Structure-Activity Relationship (SAR): Electron-withdrawing substituents like fluorine (VIe) enhanced cytotoxicity, while bulky groups reduced efficacy. Pharmacokinetics Advantage: All synthesized compounds complied with Lipinski’s Rule and exhibited excellent GI absorption—supporting their potential as orally available anticancer agents. Keyword: MCF-7 Inhibition, Thiourea Derivatives, Rescovitine, Anticancer Agents, .